358 IMAGING AND QUANTIFICATIONS OF BRAIN IRON BASED ON MAGNETIC RESONANCE SUSCEPTIBILITY. (1st January 2005) - Snissarenko, E.; Chin, V.; Anton, L.; Kim, I.; Haake, E. M.; Ayaz, M.; Khan, A.; Chong, S.; Obenaus, A.; Kido, D.; Kirsch, W. M.
Abstract : Purpose: Non-invasive (MRI) attempts to map and quantitate brain iron have been frustrated by the limitations of conventional T1, T2, and proton density imaging. Since the relationship of brain iron accumulation to the pathogenesis of a number of neurodegenerative diseases (AD = Alzheimer's Disease, PD = Parkinson's Disease) is a matter of current interest, investigating new MR imaging technology is warranted. Susceptibility weighted MR imaging (SWI) has been applied in this study to both a mouse brain model and elderly humans at risk for AD. Methods: 85 humans (54 MCI and 29 control) have had initial SWI studies and 22 have had repeated MRIs. This imaging was conducted on a 1.5T Siemens Vision System and collected data from 10 regions (motor and cingulate cortex, thalamus, hippocampus, putamen, red nuclei, substantial nigra, substantia inominata, globus pallidus, and caudate nucleus). Collected data was analyzed for iron deposits with the Spin Echo/Gradient Method. Results: Processed data is available in 24 cases with initial SWI images (10 mild cognitive impairment (MCI), 14 control), 11 cases (5 MCI, 6 control) have had follow-up scans at one year. The SWI imaging technique enables a quantitation differentiation of grey, white matter, and CSF. Though our findings remain provisional, there is only a small number of conversions from MCI to AD noted in repeat studies. This suggests a trend of enhanced iron accumulation in the red nucleus of an MCI case that converted to AD. Conclusions: This study represents the first direct correlations of a novel MR imaging technique with direct measurement of brain iron in its various forms (total, loosely bound, non-heme Fe) with extrapolation to humans. We have established that the sensitivity of the technique enables a description of phase variation for the red nuclei as an example that follow Gaussian Statistics with standard devices of about 30 units and with means for gray matter (1785 to 1855). CSF is 2075 to 2165. Any deviation about 3 S.D.'s is being considered as significant. SWI imaging proves a novel, sensitive, and apparently specific technology for the imaging and quantification of brain iron. The baseline for the study has been established and will develop with clinical follow-up over the next 3 years.